Constructivist method: Effects on achievement and retention in analytic geometry - Valdez, Jumar M. (Animo Repository, 2001)
This study attempted to investigate the effects of the constructivist teaching method on the achievement and subject matter retention in Analytic Geometry of students at Tarlac State University, Tarlac City during the second semester of school year 1999-2000. It utilized a quasi-experimental non-equivalent control group design using four intact classes of first year students pursuing Bachelor of Science in Civil Engineering and Architecture enrolled in Analytic Geometry as respondents. The experimental group was taught using the constructivist method, while the control group was taught using the traditional method of teaching. A 25-item multiple choice test developed by the researcher was used to determine the achievement of the students. The same test was administered in both the experimental and control groups before and after the treatment period to determine the subject matter retention of the students. Results of the study revealed that the students taught using the constructivist method had better achievement than the students taught using the traditional method. It was also found that the subject matter retention among the students who were taught using the constructivist method was better than the one given to the students exposed to the traditional method. The students with high mathematical ability had longer subject matter retention over those with low mathematical ability. The students whose parents are degree holders achieved better than those whose parents are non-degree holders. An interaction effect between the teaching method and parents' educational attainment was found too. No other interaction effects between and among the teaching method, mathematical ability and parents' educational attainment were significant. It can be said, therefore, that the constructivist method worked equally well with high and low mathematical ability students.